2016
DOI: 10.1136/bjophthalmol-2016-308914
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium-off versus transepithelial corneal collagen crosslinking for progressive corneal ectasia: a randomised and controlled trial

Abstract: NCT01708538; pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…They reported greater improvement in Kmax in epithelium-off group (−1.52 ± 0.66 D) compared with TE (−0.54 ± 0.58 D) with no statistically significant difference in BCVA improvement between two groups (−0.18 ± 0.09 logMAR in the conventional group versus −0.14 ± 0.08 logMAR in TE group). 103 …”
Section: Transepithelial CXL Compared To Conventional Epithelium-off mentioning
confidence: 99%
“…They reported greater improvement in Kmax in epithelium-off group (−1.52 ± 0.66 D) compared with TE (−0.54 ± 0.58 D) with no statistically significant difference in BCVA improvement between two groups (−0.18 ± 0.09 logMAR in the conventional group versus −0.14 ± 0.08 logMAR in TE group). 103 …”
Section: Transepithelial CXL Compared To Conventional Epithelium-off mentioning
confidence: 99%
“… 7 And in recent years, several clinical trials have been designed to compare the therapeutic effects between the two methods. 8 , 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Both of the surgical techniques resulted in stabilization of the CDVA during the 36-month follow-up, which is similar to the results obtained in a number of other studies, 19 although most of the comparative studies to date have reported improvement with both techniques. 8 , 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 29 Whatever the method of Rf application, however, transepithelial UVA CXL has yet to reproduce the results of traditional UVA CXL. 14 , 23 , 30 32 Specifically, a review of the literature shows that patients with transepithelial crosslinking show improved Best spectacle corrected visual acuity (BSCVA) compared to traditional crosslinking but do not show a halting of the progression of ectasia. 31 This could be due to the reduced concentration of Rf within the corneal stroma when the epithelium is left intact.…”
Section: Introductionmentioning
confidence: 99%